Anti-sway tracking control of overhead crane system based on pid and fuzzy sliding mode control - Hai, Le Xuan; Nguyen, Thai Huu; Khanh, Tran Gia; Thanh, Nguyen Tien; Duong, Bui Trong; Minh, Phan Xuan (Vietnam Journal of Science and Technology, 2017)
The paper presents a PID – Fuzzy Sliding Mode control (PID-FSMC) algorithm for overhead crane system to guarantee anti-sway trajectory tracking of the nominal plant. The proposed PID-FSMC law guarantees the closed-loop asymptotical stability as well as improveS the transient response of the load sway dynamics when the trolley is moving. The simulation results confirm the propriety of the proposed controller and show great promise of the controller application in practice.